Islamic and International Legal Perspectives on Early Child Marriage: A Bibliometric Analysis - Ateng Ruhendi; Muhamad Kholid; Agus Mailana (UIN Sunan Gunung Djati, 2026)
Early child marriage is a global issue with profound implications for children's health, education, and well-being, particularly among girls. This phenomenon remains a significant challenge in many countries, both in terms of response and academic understanding. This study aims to map the knowledge structure and research trends related to early child marriage using a bibliometric approach. The method combines quantitative and qualitative analyses, focusing on publications indexed in the Scopus database from 2013 to 2022. Data were collected using the keyword